Undifferentiated (Spindle Cell) Pancreatic Carcinoma: A Case Report with Osteochondroid Differentiation - Wang, Xing; Chen, Yong-hua; Cai, Yun-qiang; Liu, Xu-bao (JOP. Journal of the Pancreas, 2015)
Context Undifferentiated (spindle cell) carcinomas of the pancreas are rare anaplastic variants of pancreatic ductal adenocarcinoma with a frequency of 2% of pancreatic exocrine tumors. Their clinicopathological features are limited and obtained by few previously case reports. We report a case of undifferentiated pancreatic carcinoma with a rare focal osteochondroid differentiation. Case report A sixty-six-year-old woman was admitted to our hospital for abdominal pain and nonspecific nausea for almost 40 days. Imaging studies revealed a well-defined cystic–solid mass with heterogeneous density involving the tail of the pancreas. We performed an en bloc distal pancreatectomy with splenectomy for radical excision, as well as regional lymphadenectomy. The resected specimen revealed a 4.0×5.0 cm exophytic clear-bordered neoplasm of the tail of the pancreas containing necrotic and calcified areas, without splenic invasion. The lymph node involvement was not detected (0/5) and the surgical margins were negative. Microscopy showed pleomorphism with giant cells, spindle-shaped cells with anaplasia, and osteochondroid differentiation. A diagnosis of undifferentiated (spindle cell) carcinoma of the pancreas with focal osteochondroid differentiation was made. The patient declined chemotherapy and extended lymphadenectomy. She suffered from liver and lymph nodes metastasis 9 months after surgery, and she subsequently died 4 months later due to high tumor burden. Conclusions Undifferentiated pancreatic carcinoma with osteochondroid differentiation is rare but associated with extremely poor prognosis. It should be included in the differential diagnosis of pancreatic mass lesions. Image: Ossification in the tumor edge.